Management of paraproteinaemia. Issue 978 (2nd April 2007) - Cook, Lucy; Macdonald, Donald H C
Abstract : A paraprotein is a monoclonal immunoglobulin or light chain present in the blood or urine; it is produced by a clonal population of mature B cells, most commonly plasma cells. In individuals aged >50 years the incidence of a paraprotein is 3.2%. Plasma cell disorders can be considered as a spectrum of conditions ranging from monoclonal gammopathy of undetermined significance (MGUS), through asymptomatic, to symptomatic myeloma. MGUS is defined by a low level of paraprotein <30 g/l, bone marrow plasma cells <10% and the absence of myeloma related organ or tissue damage (predominantly renal, skeletal or bone marrow impairment.) MGUS requires no therapy and the overall risk of progression to myeloma is 1% per year. Myeloma remains incurable with a median survival of 3–4 years; autologous stem cell transplant can prolong survival, if appropriate. Thalidomide in combination with dexamethasone has an emerging role in the treatment of myeloma.